Une fertilisation paradoxale ? - Olivier Orain (Revue d’Histoire des Sciences Humaines)
This article offers a panoramic view of works that wondered about the influence and the consequences the events of May 1968 had on knowledge, on its institutions and on people who work on it. It mainly analyses how such works are contributing to the history of human and social studies. It first shows the precocity of the reflections on that matter and lingers over the scheme of “68 thought” that the eponym book made popular. He underlines its approximations, especially regarding causal analysis. In a second part, it lingers over the importance of the date “68” in the historiography of human sciences in the 1980’s-2000’s and over the different kinds of avoidance this branch of science shows whenever it has to handle directly the mechanisms by which the anti-establishment mood was able to change research‘s schedules. It analyses at length the exception that a seminary of the “Institute of Present Time” created in 1988, even if the broadcast of its proceedings was extremely narrow. In the third part, it proposes a program frame to systematize the survey on the consequences of the “68 years” on the staff, institutions and contents of human and social studies.